2021
DOI: 10.3389/fpls.2021.643137
|View full text |Cite
|
Sign up to set email alerts
|

Nepenthes × ventrata Transcriptome Profiling Reveals a Similarity Between the Evolutionary Origins of Carnivorous Traps and Floral Organs

Abstract: The emergence of the carnivory syndrome and traps in plants is one of the most intriguing questions in evolutionary biology. In the present study, we addressed it by comparative transcriptomics analysis of leaves and leaf-derived pitcher traps from a predatory plant Nepenthes ventricosa × Nepenthes alata. Pitchers were collected at three stages of development and a total of 12 transcriptomes were sequenced and assembled de novo. In comparison with leaves, pitchers at all developmental stages were found to be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Comparative transcriptomics analysis of leaves and leaf-derived pitcher traps from Nepenthes × ventrata identified transcriptional signatures of the transition from leaf to pitcher organ, which is akin to the evolutionary origin of the floral organ [ 25 ]. In comparison with leaves, pitchers at all developmental stages were determined to be highly enriched with genes associated with shoot apical meristem (SAM) specification/organization, stress/defense response, flowering-related MADS-box transcription factors (TFs), biosynthesis of sucrose, wax/cutin, anthocyanins, and alkaloids that are similar with flower development, apart from digestive enzymes specific to carnivory syndrome.…”
Section: Insights From Omics Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative transcriptomics analysis of leaves and leaf-derived pitcher traps from Nepenthes × ventrata identified transcriptional signatures of the transition from leaf to pitcher organ, which is akin to the evolutionary origin of the floral organ [ 25 ]. In comparison with leaves, pitchers at all developmental stages were determined to be highly enriched with genes associated with shoot apical meristem (SAM) specification/organization, stress/defense response, flowering-related MADS-box transcription factors (TFs), biosynthesis of sucrose, wax/cutin, anthocyanins, and alkaloids that are similar with flower development, apart from digestive enzymes specific to carnivory syndrome.…”
Section: Insights From Omics Studiesmentioning
confidence: 99%
“…In comparison with leaves, pitchers at all developmental stages were determined to be highly enriched with genes associated with shoot apical meristem (SAM) specification/organization, stress/defense response, flowering-related MADS-box transcription factors (TFs), biosynthesis of sucrose, wax/cutin, anthocyanins, and alkaloids that are similar with flower development, apart from digestive enzymes specific to carnivory syndrome. At the same time, the photosynthesis-related genes in pitchers were transcriptionally downregulated [ 25 ]. These transcriptomics studies showed the same developmental origins of carnivory and floral organs from leaves.…”
Section: Insights From Omics Studiesmentioning
confidence: 99%